Modernity and Psychotherapy: Two Interpretative Horizons - Cifuentes-Muñoz , Alejandro (2023)
This article aims to analyze two interpretive focuses around modernity in psychotherapy: one that describes its successes, positioning itself in favor of modernity, and another that represents its mistakes in the discipline, placing itself against it. For this, a contextual framework on modernity and psychotherapy is exposed. Then, through a hermeneutical methodology, both interpretative focuses are developed. The first (in favor) converges on how modernity has promoted the scientific status of psychotherapy, while the second (against) focuses on the epistemological implications of modernity in clinical practice. Finally, reflects on some possibilities of integration of the debate are presented through analogical hermeneutics and Feyerabend's epistemological pluralism.